Flavonoid‐producing tomato plants have a direct negative effect on the zoophytophagous biological control agent Orius sauteri. (20th June 2022) - Yang, Fengbo; Zhang, Xinyi; Shen, Haowei; Xue, Hu; Tian, Tian; Zhang, Qinghe; Hu, Jinyu; Tong, Hong; Zhang, Youjun; Su, Qi
Abstract: Orius sauteri (Poppius) (Hemiptera: Anthocoridae) is often used for biological control of small arthropod pests in greenhouse vegetable production systems in Asia. In addition to feeding on arthropod prey, O. sauteri consumes small quantities of plant material. Previous studies demonstrated that tomato plant chemistry confers antixenosis resistance to phloem‐feeding whiteflies, but the potential nontarget effects of phytochemicals on the beneficial predator O. sauteri are unknown. Comparison of O. sauteri confined to near‐isogenic lines (NILs) of tomatoes producing high levels of flavonoids (NIL‐purple hypocotyl; resistant to whiteflies) and low levels of flavonoids (NIL‐green hypocotyl; susceptible to whiteflies) revealed that O. sauteri had reduced oviposition, nymphal survival, and development on resistant plants, even if they were also provided with prey that did not feed on the host plant. Moreover, O. sauteri showed a significant ovipositional preference in choice assays, laying significantly more eggs on susceptible than on resistant plants. Molecular gut content analysis using the specific chloroplast trnL gene from tomato confirmed that adult and immature O. sauteri feed on both resistant and susceptible genotypes, and feeding behavior assays revealed that resistance did not affect plant feeding or prey acceptance by O. sauteri adults. These results demonstrate a direct negative effect of phytochemicals on a nontarget beneficial species and indicate that resistance mediated by phytochemicals can affect organisms that do not solely feed on phloem sap. The results also indicate that the mode of action and the potential ecological effects of phytochemical‐mediated resistance are broader than previously recognized. Abstract : In this study, we investigated the compatibility of whitefly‐resistant tomato (high flavonoids producing and high leaf glandular trichomes densities) with the biological control agent Orius sauteri . O. sauteri showed significantly reduced oviposition, nymphal survival, and development on resistant plants compared with susceptible plants. Furthermore, our results also indicated that this resistant genotype did not affect plant feeding or prey acceptance by adult predator. In summary, resistant tomato genotype could have a direct negative effect on the nontarget O. sauteri .